A Patient with Severe Leptospirosis Treated with Cytokine Removal and High-Dose Corticosteroids - Jure Fluher; Iva Cestar; Katja Jerenec; Žiga Kalamar; Zvonko Baklan; Andrej Markota (MDPI AG, 2022)
Leptospirosis is an ubiquitous zoonosis with significant morbidity and mortality. Approximately 10 percent of human infections evolve into a severe form, with a sepsis-like disease, multiorgan failure, and significant mortality rate. The cornerstone of treatment of severe disease is antibiotic therapy, with the aims of preventing complications, reducing the duration of disease, and ultimately reducing mortality. The initiation of antibiotic chemotherapy can precipitate a febrile inflammatory reaction, also known as a Jarisch-Herxheimer reaction. We present a case report of a patient with severe leptospirosis, complicated by multiorgan failure with severe circulatory failure of distributive and cardiogenic etiology, possibly as a consequence of the Jarisch-Herxheimer reaction. The patient was treated with antimicrobial therapy and other supportive measures along with high-dose corticosteroid therapy, long-term mechanical ventilation, high-dose vasopressor therapy, and continuous veno-venous hemodiafiltration with extracorporeal cytokine removal.With this case, we would like to report on a patient presenting with two neglected diseases in our part of Europe, who was treated with novel therapeutic strategies.